TANTANGAN DESENTRALISASI FISKAL - Lestari, Ratna Ani (Universitas Wijaya Kusuma Surabaya, 2023)
Decentralization policies must always be combined with the aim of democratizing governance, strengthening national integration, empowering local communities, respecting diversity, and improving people’s welfare. The progress of Regional Government can be seen from the ability to adapt according to current conditions, where accountability, distribution of power and authority that is used as optimally as possible is the key to the good of an area, by utilizing technology the government is required to be able to innovate, new colors and synchronize needs in society both in terms of service and product policy. On the other hand, if it is very difficult for an area to get regional income, there is nothing wrong with looking for investors for regional development, regional potential is something that can be prospected for regional progress, both potential natural resources, geography or a certain industry that requires a lot of workers who can be recruited in local community. With the HKPD Law 1/2022, the government is expected to be able to resolve the challenges of decentralization and realize an effective and efficient allocation of national resources. Key words: Decentralization policy, fiscal decentralization.